Analysis of the higher education system managerial and organizational potential in the United Republic of Tanzania with the aim of implementing a model of students’ eco-awareness formation in the Russian language - N. A. Nikitin (Вестник университета)
Russia is one of the key players in Africa. The development of diplomatic, trade, cultural relations with African countries is important in creating Russian economic relations with the outside world. In 2020–2022, during the COVID-19 pandemic, the tourist flow from Russia to Tanzania increased, which led to an increased demand for service professionals who know the Russian language. The research conducted allowed to determine the historical peculiarities of relations between Tanzania and Russia and the organizational and pedagogical potential of higher education in Tanzania with the aim of implementing a model of eco-awareness formation in the Russian language. There are 9 bachelor’s, 6 master’s and one doctoral program of training specialists in the field of natural sciences, as well as management in the field of ecology and tourism. The application of the developed training programs, as well as the model of students’ eco-awareness formation will allow to get up to 10 specialists of bachelor level (with knowledge of Russian and natural-scientific terminology) within the period of mastering the basic educational program (three years); training a specialist of master level (with knowledge of Russian and natural-scientific terminology) has a planned indicator from three to five specialists within the period of mastering the basic educational program (two years); training a specialist of doctoral level (with knowledge of Russian and natural-scientific terminology) has a planned indicator from one to two specialists. The information obtained in the course of the research is of interest for the ministries and departments of the Russian Federation in terms of planning international events and cooperation.